Clinico-epidemiological features of hypopharyngeal cancer patients presenting at Bangabandhu Sheikh Mujib medical university, Bangladesh - Samsujjaman, Khandokar; Alam, Sarwar; Bari, M. A.; Talukdhar, Sajib K.; Shams, Mohammad J.; Jha, Rajani (International Journal of Research in Medical Sciences, 2023)
Background: In Bangladesh, hypopharyngeal cancer is one of the most prevalent cancers in head neck region. In this study, the clinico-epidemiological characteristics of patients with hypopharyngeal cancer were evaluated. Methods: From November 2021 to October 2022, 172 patients with hypopharyngeal carcinoma were included in this descriptive, cross-sectional study at Bangabandhu Sheikh Mujib medical university's department of clinical oncology. During in-person interviews, data were gathered from patients using a pre-made questionnaire. Results: The mean age of the patients was 54.42 (±7.652) years, and the majority of them (59.3%) were between the ages of 51 and 60. Male patients made up 81.4% of the total patient population, and 51.16% of them were farmers. The majority of the cases (79.07%) consumed tobacco. Squamous cell carcinoma was the most prevalent histological type among the patients (92%), and most of them had a moderate degree of differentiation (65.12%). The pyriform fossa (81.4%) was the most common primary sub site. Conclusions: In conclusion, tobacco users and middle-aged men are more likely to develop hypopharyngeal cancer. The most common histological type is moderately differentiated squamous cell carcinoma, with tumours most commonly seen in the pyriform fossa of hypopharynx.